2015
DOI: 10.14393/bj-v31n6a2015-26042
|View full text |Cite
|
Sign up to set email alerts
|

Diversity among genotypes of conilon coffee selected in Espírito Santo state

Abstract: ABSTRACT:The use of multivariate techniques for factor analysis is an efficient alternative for coffee breeding programs. This study aimed to evaluate the genetic diversity of 60 genotypes of conilon coffee based on agronomic performance in the northern state of Espírito Santo and to estimate the relative contribution of different agronomic characteristics towards the diversity of the species. The data were collected in an experiment conducted on the Experimental Farm of Bananal do Norte (Instituto Capixaba de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
1
3
1
Order By: Relevance
“…Because it is characterized as quantitative, horizontal resistance presents a longer durabilty, which make it of utmost importance for genetic breeding programs aimed at resistance to leaf rust. This fact is corroborated by the different intensities of leaf rust symptoms observed in the 36 clones cultivated in this study (Table 2), as well as in a population of C. canephora cultivated at the field level (Rodrigues et al, 2012;Rodrigues et al, 2015), and under controlled conditions Mendonça et al, 2019).…”
Section: Pest and Disease Severitysupporting
confidence: 84%
See 3 more Smart Citations
“…Because it is characterized as quantitative, horizontal resistance presents a longer durabilty, which make it of utmost importance for genetic breeding programs aimed at resistance to leaf rust. This fact is corroborated by the different intensities of leaf rust symptoms observed in the 36 clones cultivated in this study (Table 2), as well as in a population of C. canephora cultivated at the field level (Rodrigues et al, 2012;Rodrigues et al, 2015), and under controlled conditions Mendonça et al, 2019).…”
Section: Pest and Disease Severitysupporting
confidence: 84%
“…Regarding the severity of leaf miners attack, no significant differences were observed among clones in all evaluated biennia (Table 3). The opposite of what was observed by Rodrigues et al (2015), which demonstrated a wide diversity concerning the attack of this pest among 40 clones of Conilon coffee. The response of variability observed among clones over the years may be related to genetic causes.…”
Section: Pest and Disease Severitycontrasting
confidence: 76%
See 2 more Smart Citations
“…Genetic variations among individuals of same or different species lead to genetic diversity, which must be ensured for sustainability of breeding programs, and continued availability of agronomically superior cultivars. Genetic diversity has been the subject of several studies in cultivated species, such as triticale (Niedziela et al, 2016), eucalyptus (Moraes et al, 2015), soybean (Ferreira Júnior et al, 2015), and coffee (Guedes et al, 2013;Silva et al, 2013;Moura et al, 2015;Rodrigues et al, 2015).…”
Section: Introductionmentioning
confidence: 99%